Enhanced Cooperation and Free Movement. Territorial Aspects of ‘Harmonisation’ - Malaga, Miłosz; Wilińska-Zelek, Anna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
In this article we examine the notion of ‘harmonisation’ in its interplay with the application of provisions on the free movement of goods. Due to the introduction of the European unitary patent protection system, we are witnessing the first cases of adopting enhanced cooperation in the internal market. This fact raises new, systemic questions concerning the concept of ‘harmonisation’ in European Union law. Are only legal, substantive aspects covered by its definition or should the territorial range of a legal act be taken into account? If yes – to what extent? Since the adoption of enhanced cooperation covers the field of intellectual property rights, the above questions concern the relationship between exercising those rights on the one hand and the principle of free movement on the other. A closer look at this matter leads to the conclusion that the unitary patent might not provide the solution to one of the problems that created for. More generally, in this article we conclude that when defining the concept of ‘harmonisation’, one should take its territorial scope into account narrowly, so as not to infringe the principles of EU law.